The Impact of Inflation and Exchange Rates on Generating Power of Cash in Egypt (Panel Data Analysis) - Elewa, May Mahmoud; Abdel aal, Yasmin Abdel aal Mahmoud; Mahmoud, Nevin Hussein Mohamed (Universitas Syiah Kuala, 2023)
Objective The objective is to study the effect of the sharp change in currency exchange rate EXR and inflation on generating power of cash GPC in light of Egyptian Accounting standards EAS in the progressing Egyptian industry setting.Methodology The methodology consists of careful examination of the numerical evidence and analysis of the changes in the relevant accounting standards and regulations. The study used numerical data from 38 non-financial firms for 5 years corresponding to 190 firm year observations during 2017-2021. The study applies the panel data method. The designated sample of firms are listed on the EGX 100, have yearly financial statements, have not discontinued during the study period, run in cash, the currency is recorded in the Egyptian pound, and have complete data. The study applies multiple regressions. It applied fixed effects, random effects, and pooled models. The study includes the dependent variables of the generating power of cash GPC. The study also includes the independent variables; exchange rates EXR and inflation rates.Results Findings indicate a significant relationship among; inflation, EXR andGPC. Findings offer new perceptions for investors and policy makers concerned with EXR and inflation.Research limitations/implications Much of the information is available. However, the time span of the study allows for tracking the impact of inflation and change in EXR on firm GPC.Novelty/Originality The originality lies in setting an accounting standard for inflation tailored for the Egyptian business environment that adapts the available accounting information to the current economic situation.